Entangled Eden: ecological change and the Lake Huron Commercial Fisheries, 1835-1978 - LaCombe, Kent (Kansas State University, 2010)
This project examines ecological change in Lake Huron during the nineteenth and twentieth century and investigates the causative role of the commercial fisheries in that change. The repeated failures of various regional and international efforts designed to improve management of the lake’s fisheries are also examined. The fundamental argument is that economic considerations were the primary motivations for policy development related to the Great Lakes fisheries. Historically management programs and legislation were shaped by local and regional economic interests. The central focus of this project is Lake Huron. Anthropogenic changes in that lake’s environment dramatically affected the lives and relationships of its non-human inhabitants. The same changes also transformed relationships among human beings who relied on the lake’s resources. Commercial fishermen who operated in the waters of both the United States and Canada relied on the lake for their livelihood, but as the twentieth century commenced the supply of marketable fishes decreased. Competition accelerated and fishermen introduced new technologies and increased their quantity of fishing gear in an effort to maximize their catches in response to fluctuating returns. Economic considerations were of primary concern to both fishermen and government bureaucrats. Lake Huron’s status as an international borderland further complicated the situation. Analysts in both the United States and Canada recognized the dramatically changing conditions of the lakes as reflected through the woes of the commercial fishery. Nonetheless, the germane state, provincial and national governments repeatedly failed in their attempts to develop a cooperative management plan. By the second half of the twentieth century Lake Huron’s embattled biome stood in stark contrast to the once seemingly endless numbers of fishes and flora that sustained the lake’s web of life for hundreds of years.
Keywords: Lake Huron; Great Lakes; environmental history; fisheries; History, General (0578)